2020
DOI: 10.3390/cells9041024
|View full text |Cite
|
Sign up to set email alerts
|

E2F1 Regulates Adipocyte Differentiation and Adipogenesis by Activating ICAT

Abstract: Wnt/β-catenin is a crucial repressor of adipogenesis. We have shown that E2 promoter binding factor 1 (E2F1) suppresses Wnt/β-catenin activity through transactivation of β-catenin interacting protein 1 (CTNNBIP1), also known as inhibitor of β-catenin and TCF4 (ICAT) in human colorectal cancers. However, it remains unknown whether ICAT is required for E2F1 to promote differentiation by inhibiting β-catenin activity in pre-adipocytes. In the present study, we found that 1-methyl-3-isobutylxanthine, dexamethasone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 53 publications
0
12
0
2
Order By: Relevance
“…Preadipocyte development and adipocyte differentiation are delicate and complicated, biological processes. With the treatment of a classical induction cocktail (MDI: 3-isobutyl-1-methylxanthine, dexamethasone, and insulin), 3T3-L1 preadipocytes were induced and to differentiate into mature adipocytes 27 , 29 . As showed in Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Preadipocyte development and adipocyte differentiation are delicate and complicated, biological processes. With the treatment of a classical induction cocktail (MDI: 3-isobutyl-1-methylxanthine, dexamethasone, and insulin), 3T3-L1 preadipocytes were induced and to differentiate into mature adipocytes 27 , 29 . As showed in Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Далее, в каноническом пути, сигнал передается на ß-катенин [4]. При активации этого пути накапливающийся свободный β-катенин проникает в ядро, где он связывается с LEF/TCF (lymphoid enhancer binding factor/T-cell specific transcription factor) и запускает транскрипцию генов-мишеней Wnt [23,24]. Wnt/β-catenin pathway ингибирует адипогенез (блокируя PPARg и CEBPA).…”
Section: Wnt и ожирениеunclassified
“…Важно отметить, что данные, полученные in vitro с использованием экспериментальных моделей, следует интерпретировать с осторожностью. К примеру, ряд исследований исключают EGR2, KLF4 из списка адипогенных факторов in vivo, объясняя это тем, что их положительное влияние на адипогенез было подтверждено лишь in vitro на 3T3-линии [16,23].…”
Section: другие регуляторы адипогенезаunclassified
“…Although these mechanisms mainly control the progression of the cell cycle (26), recent studies have reported important roles for the E2F1-pRb-CDK4 pathway beyond the sole regulation of cell proliferation (27,28). Indeed, several reports have demonstrated the role of the E2F1 pathway in the control of metabolic functions in non-proliferative cells, including adipocytes (29,30), hepatocytes (31)(32)(33), muscle and brown adipose tissue (34,35) and pancreatic b cells (17)(18)(19)36).…”
Section: Introductionmentioning
confidence: 99%